The Decision of the Most Feasible Power Plant in Underdeveloped, Remote and Outermost (3T) Region by Decision Matrix Analysis: Case Study of Pasi Island - Yoesgiantoro, Donny (International Journal of Psychosocial Rehabilitation, 2020)
Underdeveloped, remote and outermost regions (3T) are regions that have a very low indexof human development and infrastructure. One of the main factors in the development of the 3T regions is the fulfillment of the needs and potential demands of energy. The author determines three alternative power plants that can be built in the regions with low cost, able to be constructed in a short time, and do not require to be connected to the PLN's lines. The three alternative plants are PLTD, PLTS and also ESS batteries. The areas used as case studies are three (3) villages in Pasi Island, South Sulawesi Province. The analytical method used is a decision matrix analysis with primary data from questionnaires and mathematical calculations while secondary data from the literature review. The results indicated that battery ESS is the most optimal and cost-efficient choice asa power plant on Pasi Island.